Neuro-immune-endocrine mechanisms with poor adherence to aromatase inhibitor therapy in breast cancer - Huifang, Li; Jie, Gao; Yi, Feng (Frontiers in Oncology, 2022)
As the most commonly used endocrine therapy regimen for patients with hormone receptor-positive (HR+) breast cancer (BC) at present, aromatase inhibitors (AIs) reduce the risk of localized and distant recurrence, contralateral BC and secondary cancer, and prolong disease-free survival. Clinical data show that poor adherence during AI treatment is mainly attributed to muscle and joint pain, fatigue, anxiety, depression and sleep disturbances during treatment. The rapid decline of estrogen caused by AIs in a short period of time enhances sympathetic activity, activates T cells in the body, produces inflammatory factors such as tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ) and interleukin (IL)-17A, and promotes the occurrence of inflammation and bone loss. This article reviewed the mechanism of poor dependence on AIs in BC patients from the neuro-immuno-endocrine (NIE) perspective and provided clues for clinical intervention against poor adherence.